(untitled) (Research, Society and Development, 2022)
The treatment of Diabetes Mellitus (DM) through insulin therapy leads to the production of waste that, if not properly disposed of, can have negative impacts on the environment. This narrative review aims to gather evidence on how supplies related to the treatment of DM insulin users are disposed of in Brazil, in addition to discussing the importance of continuing education programs in DM for patient guidance. Google Scholar, PubMed and Scielo databases were consulted, with the guiding question “How is the disposal of supplies related to the treatment of DM by patients using insulin in Brazil?”. Results: 16 studies were included, 43.8% of which were conducted in the Southeast region and none in the North region. The most frequent disposal of inputs was common waste, and in most studies, patients reported not having been sufficiently well oriented on how to proceed after using the inputs related to the treatment. Conclusion: In Brazil, individuals with insulin-dependent DM, for the most part, dispose of supplies related to the treatment of the disease inappropriately, bringing potential risks to the environment. The low supply of health education programs is a factor that contributes to this fact and, therefore, actions focused on the importance of conscious use of inputs, as well as the correct form of their disposal is latent. Understanding the importance of good DM control is as important as the concern with the packaging of waste formed by treatment residues.